Demand Pattern Analysis of Broilers by Satay Madura Sellers in Bandar Lampung City - Indah Febrialita Putri; Teguh Endaryanto; Lina Marlina (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
The purpose of this study is to determine the pattern of demand for broilers and the factors that influence the demand for broilers by Madura satay traders in Bandar Lampung City. This study uses a survey method. The sample is taken using a proportional random sampling technique with the number of respondents being 31 traders. Furthermore, the analytical method used is descriptive analysis and multiple linear regression with the Ordinary Least Square (OLS) Regression method. The result of the research shows that the pattern of demand for broilers by Madura satay traders in Bandar Lampung City consists of the frequency of purchase, the average number of purchases, and the place of purchase. The frequency of purchases made by Madura satay traders is seven times a week with an average number of purchases of 31 kg per week. Then, the usual place to make a purchase is the chicken trader in the market. The factors that significantly affect the demand for broilers are the price of chicken, the price of peanuts, the price of charcoal, and the price of output.